Recognition of Construction Contract Revenue based on PSAK 34 at PT Tunggal Jaya Raya - Firdaus Indra Faradiba; Sulis Rochayatun (Journal of Contemporary Information Technology, Management, and Accounting, 2020)
All companies have the aim to get profit with maximum. One of the elements related to the acquisition of profit is income. In each type of company certainly have different methods in recognizing its income. In the construction company there are two ways of revenue recognition namely completion percentage and contract completion. This research aims to determine how the revenue recognition of the construction contracts used by PT Tunggal Jaya Raya. This research uses qualitative research methods. The results showed that the company in recognizing its earnings on the basis of cash receipts or cash bases, with a period of 4 months. The company is working on a project with a period of 4 months using the system, but the record is not in accordance with PSAK No. 34. The conclusion of this research is that the company in recognizing the income of contracts if using recognition by the method of settlement percentage preferably with a cost approach so that the value of income and profit value can be recognized more precisely. However, looking at the project time period of 4 months, the company should use the completed contract method.